PERANCANGAN INDOOR MODULAR BOOTH DISPLAY UNTUK PRODUK PAKAIAN ARDHINA BATIK GORGA - Rani Hermita; John John; Wahyuni Latifah (Lembaga Pengembangan Kinerja Dosen, 2023)
The growing development of shopping centers in the city of Medan creates business opportunities, starting from creating innovations in business opportunities. Currently, there are many kinds of markets emerging to accommodate business people, both new and old. So that many design problems have arisen in the display booth, the selection of appropriate materials and construction systems so as to answer the need for displays that have many functions (multifunctional), namely as accommodation for clothing display needs that are easy to disassemble (knockdown). In addition, to market their products, this market activity is an alternative to promote their brand, so that it can be known by the wider community. The method used in this design starts from the empathize and define stages starting from data collection, direct observation and interviews, both to tenants and pop-up market organizers. After the data collection stage is complete, the existing data is then analyzed. Then proceed to the ideate stage, through the process of brainstorming ideas, solving a problem, and determining the values ​​of the design. After the ideate stage, proceed to the prototype stage, where the process of visualizing ideas to get the desired results to the manufacturing stage is realized in the form of a prototype with a scale of 1:1. After the prototype is finished, a test is carried out to get feedback from users and refined through the implementation stage to perfect the product. The result of this design is that products that have been designed are oriented to be transformed into various models from the same material, with functions that can accommodate the needs of clothing displays that are still fulfilled in each module. The application of the modular concept is applied with a knockdown system, using a stalbuis pipe consisting of 3 sizes, namely, 40 cm, 21.2 cm, and 20 cm. To connect the stalbuis pipe using uno joker connections, nuts and bolts connections, and inner connections. As a flat cross section using canvas tarpaulin which consists of 2 sizes, namely, 13 cm x 51 cm and 4 cm x 51 cm.